What rural people in Tamilnadu are doing to prevent dengue? - Pattnaik, Satyajit; Selvaraj, Kokila (International Journal Of Community Medicine And Public Health, 2017)
Background: Traditionally dengue was perceived as an urban problem. But of late many cases are being reported from rural areas. This study was undertaken to assess the preventive measures taken by people in a rural area against dengue. Methods: This was a cross sectional study done in the rural field practice area of a private medical college in Tamilnadu. Hundred houses were selected from five villages through a multi stage simple random sampling. A pre-tested semi-structured interview schedule was used for data collection. Results: All household surveyed reported using some form of personal measures against dengue. The most common personal protective measure was use of mosquito nets (58%) followed by mosquito coils (9%). Almost all (98%) of the respondents use the PPM at night time only. Conclusions: It was found that many people are using PPMs but mostly during the daytime. This practice has to be corrected with more awareness and health education.